Tetralogy of Fallot with Anomalous Left Anterior Descending Coronary Artery :A Rare Repair A Case Report and Review of Literature - Rahman, Md Mazibur; Roy, Siba Pada; Uddin, Jalal (University Heart Journal, 2015)
Surgical total correction of Fallots tetralogy (TOF) with coronary artery anomalies is associated with an increased risk for mortality and morbidity. We performed Trans-ventricular and Trans-annular autologous pericardial patchplasty with the incorporation of a monocusp valve at pulmonary annular level after excision of parietal and septal bands and anastomosis of left internal mammary artery (LIMA) at the distal segment of deliberately sacrificed left anterior descending coronary artery (LAD) in a 20-year young male patient in whom the LAD coronary artery arose from the right sinus of valsalva anomalously just next to the right coronary artery (RCA). The large ventricular septal defect (VSD) was closed with Dacron patch but the small atrial septal defect (ASD) was closed directly with suture. A large patent ductus arteriosus (PDA) and a major aortopulmonary collateral (MAPCA) were ligated before cardiopulmonary bypass (CPB). The patient was discharged without any problem. University Heart Journal Vol. 10, No. 2, July 2014; 97-101